Democracy and Development in Southeast Asia: A Critical Comparison - M Faishal Aminuddin; Joko Purnomo (Parahyangan Center for International Studies, 2019)
ABSTRACTThere is an intriguing debate relating to the relationship of economic development to democratization. Southeast Asia region is one of the fast-growing economic development, and it also has a long journey to democratization. The result, however, is ambiguous regarding the internal dynamic of this region that hinders the possibility to have consolidated democracy. However, an achievement in economic development might facilitate political development. This paper will provide a critical note about the relationship between development and the political regime in the SEA region. This paper also analyzes the reason why there is no significant change regarding political regime within this region even though some countries are continuing to have positive achievements in democratization. Also, autocracy and the authoritarian regime still survive in this region. This paper assesses the progress of social and economic development and its impacts on domestic politics, then, attempts to explain the process of political transformation in the SEA region to understand the causes that hinder the spreading of democratization. Qualitative method will be used to analyze data and provide conclusion of this study.Keywords: democratization, development, political transformation, SEA countries